Structure of nanoporous zirconia-based powders synthesized by different gel-combustion routes - Casanova, Jorge R.; Fabregas, Ismael O.; Lamas, Diego G.; de Reca, Noemi E. Walsoe; Lascalea, Gustavo E.; Kempf, Rodolfo; Craievich, Aldo F.; Santilli, Celso Valentim [UNESP] (Blackwell Publishing, 2007)
Zirconia-based ceramics that retain their metastable tetragonal phase at room temperature are widely studied due to their excellent mechanical and electrical properties. When these materials are prepared from precursor nanopowders with high specific surface areas, this phase is retained in dense ceramic bodies. In this work, we present a morphological study of nanocrystalline ZrO2-2.8 mol% Y2O3 powders synthesized by the gel-combustion method, using different organic fuels - alanine, glycine, lysine and citric acid - and calcined at temperatures ranging from 873 to 1173 K. The nanopore structures were investigated by small-angle X-ray scattering. The experimental results indicate that nanopores in samples prepared with alanine, glycine and lysine have an essentially single-mode volume distribution for calcination temperatures up to 1073 K, while those calcined at 1173 K exhibit a more complex and wider volume distribution. The volume-weighted average of the nanopore radii monotonically increases with increasing calcination temperature. The samples prepared with citric acid exhibit a size distribution much wider than the others. The Brunauer-Emmett-Teller technique was used to determine specific surface area and X-ray diffraction, environmental scanning electron microscopy and transmission electron microscopy were also employed for a complete characterization of the samples.